Predictors of congestive heart failure in the elderly: the Cardiovascular Health Study. - Gottdiener, J S; Arnold, A M; Aurigemma, G P; Polak, J F; Tracy, R P; Kitzman, D W; Gardin, J M; Rutledge, J E; Boineau, R C (J Am Coll Cardiol, 2000)
OBJECTIVES: We sought to characterize the predictors of incident congestive heart failure (CHF), as determined by central adjudication, in a community-based elderly population. BACKGROUND: The elderly constitute a growing proportion of patients admitted to the hospital with CHF, and CHF is a leading source of morbidity and mortality in this group. Elderly patients differ from younger individuals diagnosed with CHF in terms of biologic characteristics. METHODS: We analyzed data from the Cardiovascular Health Study, a prospective population-based study of 5,888 elderly people >65 years old (average 73 +/- 5, range 65 to 100) at four locations. Multiple laboratory measures of cardiovascular structure and function, blood chemistries and functional assessments were obtained. RESULTS: During an average follow-up of 5.5 years (median 6.3), 597 participants developed incident CHF (rate 19.3/1,000 person-years). The incidence of CHF increased progressively across age groups and was greater in men than in women. On multivariate analysis, other independent predictors included prevalent coronary heart disease, stroke or transient ischemic attack at baseline, diabetes, systolic blood pressure (BP), forced expiratory volume 1 s, creatinine >1.4 mg/dl, C-reactive protein, ankle-arm index <0.9, atrial fibrillation, electrocardiographic (ECG) left ventricular (LV) mass, ECG ST-T segment abnormality, internal carotid artery wall thickness and decreased LV systolic function. Population-attributable risk, determined from predictors of risk and prevalence, was relatively high for prevalent coronary heart disease (13.1%), systolic BP > or =140 mm Hg (12.8%) and a high level of C-reactive protein (9.7%), but was low for subnormal LV function (4.1%) and atrial fibrillation (2.2%). CONCLUSIONS: The incidence of CHF is high in the elderly and is related mainly to age, gender, clinical and subclinical coronary heart disease, systolic BP and inflammation. Despite the high relative risk of subnormal systolic LV function and atrial fibrillation, the actual population risk of these for CHF is small because of their relatively low prevalence in community-dwelling elderly people.
Keywords: Aged; Aged, 80 and over; Coronary Disease; Female; Geriatric Assessment; Heart Failure; Humans; Ischemic Attack, Transient; Male; Prospective Studies; Risk Factors; Survival Rate

Predictive value of systolic and diastolic function for incident congestive heart failure in the elderly: the cardiovascular health study. - Aurigemma, G P; Gottdiener, J S; Shemanski, L; Gardin, J; Kitzman, D (J Am Coll Cardiol, 2001)
OBJECTIVES: We sought to assess the ability of echocardiographic indices of systolic and diastolic function to predict incident congestive heart failure (CHF). BACKGROUND: Noninvasive indices of subclinical systolic and/or diastolic dysfunction that can be used to identify patients in a transition phase between normal cardiac function and clinical CHF would be valuable. Though midwall shortening and Doppler mitral inflow patterns are seemingly well suited to predict subsequent CHF, the predictive value of these indices has not been investigated. METHODS: We studied 2,671 participants in the Cardiovascular Health Study who were free of coronary heart disease, CHF or atrial fibrillation. Clinical and quantitative echocardiographic data were obtained in all participants. RESULTS: At a mean follow-up of 5.2 years (range 0 to 6 years), 170 participants (6.4% of the cohort) developed CHF. Although 96% of these participants had normal or borderline ejection fraction (EF) at baseline, only 57% had normal or borderline EF at the time of hospitalization. In multivariate modeling, fractional shortening at the endocardium (relative risk [RR] 1.85 per 10-unit decrease, confidence interval [CI] 1.27 to 2.39), fractional shortening at the midwall (RR 1.29 per five-unit decrease, 95% CI 1.11-1.51) and peak Doppler peak E (RR 1.15 for each 0.1 M/s increment; CI 1.02 to 1.21) independently predicted incident CHF. Both high and low Doppler E/A ratios were predictive of incident CHF. CONCLUSIONS: Roughly half the occurrences of CHF in this population are associated with normal or borderline EF. Echocardiographic findings suggestive of subclinical contractile dysfunction and diastolic filling abnormalities are both predictive of subsequent CHF. The standard (FSendo) and refined (FSmw) parameters of systolic function performed similarly in this regard, though subjects with left ventricular hypertrophy and depressed FSmw are at particularly high risk for subsequent CHF.
Keywords: Age Factors; Aged; Aged, 80 and over; Diastole; Echocardiography; Female; Follow-Up Studies; Heart Failure; Humans; Male; Multivariate Analysis; Myocardial Contraction; Predictive Value of Tests; Prognosis; Proportional Hazards Models; Risk Factors; Systole